Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1174
|View full text |Cite
|
Sign up to set email alerts
|

Off-Topic Spoken Response Detection Using Siamese Convolutional Neural Networks

Abstract: In this study, we developed an off-topic response detection system to be used in the context of the automated scoring of nonnative English speakers' spontaneous speech. Based on transcriptions generated from an ASR system trained on non-native speakers' speech and various semantic similarity features, the system classified each test response as an on-topic or off-topic response. The recent success of deep neural networks (DNN) in text similarity detection led us to explore DNN-based document similarity feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…It is able to learn high-level representations of inputs from their respective sub-networks for further comparison. The inputs for Siamese network can be image data, sentences or sequential data, and thus the model is applicable to various comparison-making tasks such as image matching (e.g., face [40] and signature [41] verifications) and semantic matching (e.g., community question answering [42], off-topic response detection [43]). In this work, a siamese network is trained to compare spoken stories from impaired speakers and unimpaired ones for the text feature extraction.…”
Section: B Siamese Network: Aphasic Speech Vs Unimpaired Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…It is able to learn high-level representations of inputs from their respective sub-networks for further comparison. The inputs for Siamese network can be image data, sentences or sequential data, and thus the model is applicable to various comparison-making tasks such as image matching (e.g., face [40] and signature [41] verifications) and semantic matching (e.g., community question answering [42], off-topic response detection [43]). In this work, a siamese network is trained to compare spoken stories from impaired speakers and unimpaired ones for the text feature extraction.…”
Section: B Siamese Network: Aphasic Speech Vs Unimpaired Speechmentioning
confidence: 99%
“…The model architecture adopted in this study is motivated by that in [43], which is shown in Fig. 6.…”
Section: ) Architecture Of Siamese Networkmentioning
confidence: 99%
“…In order to compare the performance of the content features with the speech-driven features, we trained three models: Speech (model based on 35 speech-driven features), Content (model based on 28 content features), and ALL (model based on both speech-driven and content features, 63 features in total). Finally, a total of 6 models (3 feature groups * 2 training data sets) were trained using the Random-ForestRegressor algorithm 6 in scikit-learn [20].…”
Section: Methodsmentioning
confidence: 99%
“…Even state-of-the art automated scoring models face challenges in scoring these atypical responses [1,2,3], and researchers in the automated scoring field have tried to solve this issue using a two-step approach where an automated filtering model, as a sub-module of an automated scoring system, filters out atypical responses, and only the remaining responses are scored by the scoring model. A spoken canned response detection system in [4], an off-topic response detection system in [5,6] and a coherence model in [7] are examples of this approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation